Composite grouting material for underground goaf and preparation method of composite grouting material
By preparing a composite grouting material for underground goaf composed of components A and components B, the problems of high cost of polymer grouting materials and poor sealing effect are solved, and efficient goaf repair is achieved , has excellent mechanical properties and flame retardant effect.
Patent Information
- Application Number
- CN202411671515.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, high polymer grouting materials are costly, unable to effectively seal the water inlet in the goaf, and are used less frequently in emergency rescue.
Provided is a composite grouting material made of components A and components B, which include polyols, foaming agents, catalysts and ordinary silicate cement, and component B includes polyisocyanate, reinforcement The agent, a modifier and a flame retardant are prepared by a solvent-heat reaction, and mixed with a reinforcement and a flame retardant to form a grouting material with excellent mechanical properties and flame retardant effect.
It significantly improves the compressive strength and bending strength after curing, has excellent corrosion resistance and explosion resistance, can effectively reduce ground settlement, improve the bearing capacity of the foundation, and has the flame retardant effect of self-extinguishing without fire.
Smart Images

Figure BDA0005145976520000071 
Figure BDA0005145976520000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grouting materials, and in particular to an underground goaf area composite grouting material and a preparation method thereof. Background Art
[0002] During the ore mining process, underground ore needs to be transported to the ground to form a reasonable transportation and mining operation surface. As the ore is continuously transported out, mining goafs are formed underground. If the goaf is idle for a long time, it will cause the risk of roof rock collapse and cause surface collapse. How to repair the goaf has become the top priority of current goaf engineering construction. Common grouting materials for goafs usually use cement-water glass, cement-fly ash, polymers, etc. When water gushes from the goaf, cement-water glass and cement-fly ash cannot be blocked, and polymers are very expensive and are usually only used for emergency rescue. Therefore, it is of great significance to study a composite grouting material for underground goafs and its preparation method. Summary of the invention
[0003] The object of the present invention is to provide a composite grouting material for underground goaf areas and a preparation method thereof, so as to solve the problem of high cost of polymer grouting materials in the prior art.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a composite grouting material for underground goaf areas, wherein the composite grouting material for underground goaf areas is made of component A and component B, wherein the weight ratio of component A to component B is 0.6 to 1.1:1;
[0006] The component A comprises the following raw materials in parts by weight: 50-100 parts of polyol, 0.3-0.8 parts of foaming agent, 1.5-3 parts of catalyst, 120-150 parts of ordinary Portland cement, and 60-80 parts of water;
[0007] The B component includes the following raw materials in parts by weight: 35-55 parts of polyisocyanate, 35-50 parts of reinforcing agent, 2-8 parts of modifier, and 5-15 parts of flame retardant;
[0008] The modifier is made of trimesic acid, magnesium salt and tetrabutyl titanate.
[0009] Preferably, the polyol is a polyether polyol and / or a polyester polyol.
[0010] Preferably, the foaming agent comprises one or more of monofluorodichloroethane, trifluorodichloroethane, trifluorotrichloroethane, pentafluoropropane, pentachlorobutane, cyclopentane, n-pentane and perfluoroheptane.
[0011] Preferably, the catalyst is an organic metal catalyst and an amine catalyst; the organic metal catalyst is stannous octoate, dibutyltin dilaurate or bismuth isooctanoate; the amine catalyst is triethylenediamine, N,N-dimethylcyclohexylamine, triethylenediamine, triethanolamine or pentamethyldiethylenetriamine.
[0012] Preferably, the polyisocyanate comprises one or more of toluene-2,4-diisocyanate, carbodiimide-modified diphenylmethane diisocyanate and isophorone diisocyanate.
[0013] Preferably, the reinforcing agent comprises one or more of nano calcium carbonate, nano silicon dioxide and glass fiber.
[0014] Preferably, the flame retardant comprises one or more of triethyl phosphate, dimethyl methyl phosphate, triisopropylphenyl phosphate, dibromoneopentyl glycol, ammonium polyphosphate and ammonium molybdate.
[0015] Preferably, the method for preparing the modifier comprises the following steps: tetrabutyl titanate, magnesium salt and trimesic acid are mixed in methanol for solvent thermal reaction to obtain the modifier.
[0016] Preferably, the mass ratio of tetrabutyl titanate, magnesium salt and trimesic acid is 3-5:1-4:1-3; the mass volume ratio of magnesium salt and methanol is 1-4g:50-120mL; the temperature of the solvent thermal reaction is 100-120°C, and the time of the solvent thermal reaction is 1-3h.
[0017] The present invention also provides a method for preparing the above-mentioned underground mining composite grouting material, comprising the following steps:
[0018] (1) ordinary Portland cement and water are mixed, and then a polyol, a foaming agent and a catalyst are added and mixed to obtain component A;
[0019] (2) mixing polyisocyanate, reinforcing agent, modifier and flame retardant to obtain component B;
[0020] (3) Component A and component B are mixed according to a weight ratio to obtain a composite grouting material for underground goaf areas.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention uses tetrabutyl titanate, magnesium salt and trimesic acid to prepare a modifier, and then adds the modifier and the reinforcing agent to the underground goaf composite grouting material, which can significantly improve the compressive strength and flexural strength of the underground goaf composite grouting material after solidification.
[0023] (2) The present invention adds the compounded flame retardant to the composite grouting material of the underground goaf, which can significantly improve the flame retardant effect.
[0024] (3) The underground goaf composite grouting material of the present invention has excellent corrosion resistance and explosion resistance.
[0025] (4) The composite grouting material for underground goaf of the present invention has excellent mechanical properties. It can be used to repair goaf, effectively reduce ground settlement, and improve the bearing capacity of the foundation. The repaired goaf can be used again for engineering construction. DETAILED DESCRIPTION
[0026] The present invention provides a composite grouting material for underground goaf areas, wherein the composite grouting material for underground goaf areas is made of component A and component B, wherein the weight ratio of component A to component B is 0.6 to 1.1:1;
[0027] The component A comprises the following raw materials in parts by weight: 50-100 parts of polyol, 0.3-0.8 parts of foaming agent, 1.5-3 parts of catalyst, 120-150 parts of ordinary Portland cement, and 60-80 parts of water;
[0028] The B component includes the following raw materials in parts by weight: 35-55 parts of polyisocyanate, 35-50 parts of reinforcing agent, 2-8 parts of modifier, and 5-15 parts of flame retardant;
[0029] The modifier is made of trimesic acid, magnesium salt and tetrabutyl titanate.
[0030] In the present invention, the weight ratio of the component A to the component B is preferably 0.7 to 1.0:1, and more preferably 0.8 to 0.9:1.
[0031] In the present invention, the weight proportion of the polyol is preferably 55 to 95 parts, more preferably 60 to 90 parts; the polyol is a polyether polyol and / or a polyester polyol, preferably a mixture of a polyether polyol and a polyester polyol, and the mass ratio of the polyether polyol to the polyester polyol is 2 to 4:1, preferably 3:1.
[0032] In the present invention, the polyether polyol is trimethylolpropane polyether polyol, sorbitol polyether polyol or glycerol polyether polyol; and the polyester polyol is phthalic anhydride polyester polyol.
[0033] In the present invention, the weight portion of the foaming agent is preferably 0.4 to 0.7 parts, and more preferably 0.5 to 0.6 parts; the foaming agent comprises one or more of monofluorodichloroethane, trifluorodichloroethane, trifluorotrichloroethane, pentafluoropropane, pentachlorobutane, cyclopentane, n-pentane and perfluoroheptane, preferably one or more of pentachlorobutane, cyclopentane, n-pentane and perfluoroheptane, and more preferably one or more of cyclopentane, n-pentane and perfluoroheptane.
[0034] In the present invention, the weight of the catalyst is preferably 1.8 to 2.5 parts, and more preferably 2.0 to 2.2 parts; the catalyst is an organic metal catalyst and an amine catalyst; the organic metal catalyst is stannous octoate, dibutyltin dilaurate or bismuth isooctanoate, preferably stannous octoate or dibutyltin dilaurate, and more preferably dibutyltin dilaurate; the amine catalyst is triethylenediamine, N,N-dimethylcyclohexylamine, triethylenediamine, triethanolamine or pentamethyldiethylenetriamine, preferably triethylenediamine, triethanolamine or pentamethyldiethylenetriamine, and more preferably triethanolamine or pentamethyldiethylenetriamine; the mass ratio of the organic metal catalyst to the amine catalyst is 2.5 to 4:1, preferably 2.8 to 3.5:1, and more preferably 3 to 3.2:1.
[0035] In the present invention, the weight of the ordinary Portland cement is preferably 125 to 145 parts, more preferably 130 to 140 parts; the weight of the water is preferably 65 to 75 parts, more preferably 70 parts.
[0036] In the present invention, the weight proportion of the polyisocyanate is preferably 40 to 50 parts, more preferably 42 to 48 parts; the polyisocyanate comprises one or more of toluene-2,4-diisocyanate, carbodiimide-modified diphenylmethane diisocyanate and isophorone diisocyanate, preferably toluene-2,4-diisocyanate and / or isophorone diisocyanate, more preferably isophorone diisocyanate.
[0037] In the present invention, the weight of the reinforcing agent is preferably 38 to 48 parts, more preferably 40 to 45 parts; the reinforcing agent comprises one or more of nano-calcium carbonate, nano-silicon dioxide and glass fiber, preferably nano-silicon dioxide and / or glass fiber, more preferably glass fiber.
[0038] In the present invention, the weight proportion of the flame retardant is preferably 7 to 12 parts, more preferably 8 to 10 parts; the flame retardant comprises one or more of triethyl phosphate, dimethyl methyl phosphate, triisopropylphenyl phosphate, dibromoneopentyl glycol, ammonium polyphosphate and ammonium molybdate, preferably one or more of dimethyl methyl phosphate, triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate, more preferably a mixture of triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate, and the mass ratio of triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate is 1 to 2:1 to 2:3, more preferably 1:1:3.
[0039] In the present invention, the weight portion of the modifier is preferably 3 to 7 parts, more preferably 4 to 6 parts.
[0040] In the present invention, the preparation method of the modifier comprises the following steps: tetrabutyl titanate, magnesium salt and trimesic acid are mixed in methanol for solvent thermal reaction to obtain the modifier.
[0041] In the present invention, the mass ratio of tetrabutyl titanate, magnesium salt and trimesic acid is 3-5:1-4:1-3, preferably 3.5-4.5:1.5-3.5:2, and more preferably 3:2-3:2; the mass volume ratio of the magnesium salt and methanol is 1-4g:50-120mL, preferably 1.5-3.5g:70-110mL, and more preferably 2-3g:80-100mL; the temperature of the solvent thermal reaction is 100-120°C, preferably 105-115°C, and more preferably 110-120°C; the time of the solvent thermal reaction is 1-3h, preferably 1.5-2.5h, and more preferably 2h.
[0042] In the present invention, the magnesium salt comprises magnesium nitrate and / or magnesium chloride, preferably magnesium nitrate.
[0043] The present invention also provides a method for preparing the above-mentioned underground mining composite grouting material, comprising the following steps:
[0044] (1) ordinary Portland cement and water are mixed, and then a polyol, a foaming agent and a catalyst are added and mixed to obtain component A;
[0045] (2) mixing polyisocyanate, reinforcing agent, modifier and flame retardant to obtain component B;
[0046] (3) Component A and component B are mixed according to a weight ratio to obtain a composite grouting material for underground goaf areas.
[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] The ordinary Portland cement used in Examples 1 to 3 and Comparative Examples 1 to 3 is ordinary Portland cement 42.5R.
[0049] Example 1
[0050] 3 g of tetrabutyl titanate, 3 g of magnesium nitrate, 2 g of trimesic acid and 70 mL of methanol were mixed evenly, then transferred to a reactor and reacted at 110° C. for 2 h. The hydrothermal reaction product was washed three times with deionized water and finally dried in a constant temperature drying oven at 60° C. for 12 h to obtain a modifier.
[0051] The raw materials of component A are as follows: 60 parts of POLYOLTP-390 trimethylolpropane polyether polyol (purchased from Shanghai Yexing Industrial Co., Ltd.), 20 parts of RAYNOLPF2012 phthalic anhydride polyester polyol (purchased from Qingdao Ruinuo Chemical Co., Ltd.), 0.5 parts of n-pentane as a foaming agent, 2 parts of a catalyst (including 1.5 parts of dibutyltin dilaurate and 0.5 parts of pentamethyldiethylenetriamine), 135 parts of ordinary Portland cement, and 70 parts of water.
[0052] The raw material composition of component B is as follows: 45 parts of isophorone diisocyanate, 42 parts of reinforcing agent glass fiber, 4 parts of modifier, and 10 parts of flame retardant (2 parts of triisopropylphenyl phosphate, 2 parts of dibromoneopentyl glycol, and 6 parts of ammonium molybdate).
[0053] Preparation method: ordinary Portland cement and water are mixed evenly, trimethylolpropane polyether polyol, phthalic anhydride polyester polyol, n-pentane, dibutyltin dilaurate, pentamethyldiethylenetriamine are added at a stirring speed of 500 rpm, and then stirred for 1 hour to obtain component A;
[0054] isophorone diisocyanate, glass fiber, a modifier, triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate were mixed, and stirred at a stirring speed of 500 rpm for 30 minutes to obtain a component B;
[0055] The components A and B are mixed evenly in a weight ratio of 0.8:1 to obtain a composite grouting material for underground goaf areas.
[0056] Example 2
[0057] 3 g of tetrabutyl titanate, 3 g of magnesium nitrate, 2 g of trimesic acid and 70 mL of methanol were mixed evenly, then transferred to a reactor and reacted at 110° C. for 2 h. The hydrothermal reaction product was washed three times with deionized water and finally dried in a constant temperature drying oven at 60° C. for 12 h to obtain a modifier.
[0058] The raw materials of component A are as follows: 40 parts of F3135 glycerol polyether polyol (purchased from Shandong Wanhua Polyurethane Co., Ltd.), 10 parts of RAYNOL PF2012 phthalic anhydride polyester polyol (purchased from Qingdao Ruinuo Chemical Co., Ltd.), 0.3 parts of cyclopentane as a foaming agent, 2.5 parts of a catalyst (including 2 parts of stannous octoate and 0.5 parts of triethanolamine), 120 parts of ordinary Portland cement, and 60 parts of water.
[0059] The raw material composition of component B is: 35 parts of toluene-2,4-diisocyanate, 35 parts of reinforcing agent nano-silica, 8 parts of modifier, 6 parts of flame retardant (1 part of triisopropylphenyl phosphate, 2 parts of dibromoneopentyl glycol, 3 parts of ammonium molybdate).
[0060] Preparation method: ordinary Portland cement and water are mixed evenly, glycerol polyether polyol, phthalic anhydride polyester polyol, cyclopentane, stannous octoate and triethanolamine are added at a stirring speed of 600 rpm, and then stirred for 1 hour to obtain component A;
[0061] Toluene-2,4-diisocyanate, nano-silica, a modifier, triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate were mixed, and stirred at a stirring speed of 500 rpm for 40 minutes to obtain a component B;
[0062] The components A and B are mixed evenly in a weight ratio of 0.6:1 to obtain a composite grouting material for underground goaf areas.
[0063] Example 3
[0064] 3 g of tetrabutyl titanate, 4 g of magnesium nitrate, 2 g of trimesic acid and 100 mL of methanol were mixed evenly, then transferred to a reactor and reacted at 100° C. for 2 h. The hydrothermal reaction product was washed three times with deionized water and finally dried in a constant temperature drying oven at 60° C. for 12 h to obtain a modifier.
[0065] The raw materials of component A are as follows: 75 parts of 6305C sorbitol polyether polyol (purchased from Jurong Ningwu New Materials Development Co., Ltd.), 25 parts of RAYNOL PF2012 phthalic anhydride polyester polyol (purchased from Qingdao Ruinuo Chemical Co., Ltd.), 0.8 parts of perfluoroheptane as a foaming agent, 3 parts of a catalyst (including 2.25 parts of bismuth isooctanoate and 0.75 parts of triethylenediamine), 150 parts of ordinary Portland cement, and 80 parts of water.
[0066] The raw material composition of component B is: 50 parts of carbodiimide modified diphenylmethane diisocyanate, 50 parts of reinforcing agent nano calcium carbonate, 2 parts of modifier, 15 parts of flame retardant (3.75 parts of triisopropylphenyl phosphate, 3.75 parts of dibromoneopentyl glycol, 7.5 parts of ammonium molybdate).
[0067] Preparation method: ordinary Portland cement and water are mixed evenly, sorbitol polyether polyol, phthalic anhydride polyester polyol, perfluoroheptane, bismuth isooctanoate, and triethylenediamine are added at a stirring speed of 600 rpm, and then stirred for 1 hour to obtain component A;
[0068] Carbodiimide-modified diphenylmethane diisocyanate, nano-calcium carbonate, a modifier, triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate were mixed, and stirred at a stirring speed of 500 rpm for 40 minutes to obtain a component B;
[0069] Component A and component B are mixed evenly in a weight ratio of 1.1:1 to obtain a composite grouting material for underground goaf areas.
[0070] Comparative Example 1
[0071] The difference from Example 1 is that no modifier is added to the raw materials of component B, and other conditions are the same.
[0072] Comparative Example 2
[0073] The difference from Example 1 is that no reinforcing agent is added to the raw materials of component B, and other conditions are the same.
[0074] Comparative Example 3
[0075] The difference from Example 1 is that the flame retardant in the raw materials of component B is 8 parts of triisopropylphenyl phosphate and 2 parts of dibromoneopentyl glycol, and no ammonium molybdate is added. Other conditions are the same.
[0076] Performance Verification:
[0077] The underground goaf composite grouting materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were poured into a mold and tested after curing for 24 hours.
[0078] The mechanical properties of the cured underground goaf composite grouting material were tested in accordance with ASTM D3501-05 and 3499-11 “Standards for Testing Mechanical Properties of Materials”. The test results are shown in Table 1.
[0079] In accordance with AQ / T 1089-2020 "Polymer Materials for Reinforcement of Coal Rock in Coal Mines", the flame retardancy of the composite grouting materials in underground goaf areas was tested. The test results are shown in Table 1.
[0080] Table 1 Test results of Examples 1 to 3 and Comparative Examples 1 to 3
[0081]
[0082]
[0083] It can be seen from Table 1 that the compressive strength and flexural strength of the composite grouting material for underground goaf after solidification can be significantly enhanced by adding modifiers and reinforcing agents. Adding the flame retardant compounded with triisopropylphenyl phosphate, dibromoneopentyl glycol and ammonium molybdate to the composite grouting material for underground goaf has a better flame retardant effect and achieves a self-extinguishing state when away from fire.
[0084] The composite grouting material for underground goaf prepared in Examples 1 to 3 was poured into a mold and cured for 24 hours to obtain a composite grouting material test block. The corrosion resistance of the test block was measured. The test method was: the test block prepared above was immersed in a 10% hydrochloric acid solution or a 10% sodium hydroxide solution for 168 hours. It was found that the test block did not show cracking or collapse, which indicates that the composite grouting material for underground goaf of the present invention has excellent corrosion resistance.
[0085] It can be seen from the above embodiments that the present invention provides a composite grouting material for underground goaf and a preparation method thereof. The composite grouting material for underground goaf of the present invention is made of component A and component B, and the weight ratio of component A to component B is 0.6-1.1:1; the component A includes the following raw materials in parts by weight: 50-100 parts of polyol, 0.3-0.8 parts of foaming agent, 1.5-3 parts of catalyst, 120-150 parts of ordinary Portland cement, and 60-80 parts of water; the component B includes the following raw materials in parts by weight: 35-55 parts of polyisocyanate, 35-50 parts of reinforcing agent, 2-8 parts of modifier, and 5-15 parts of flame retardant; wherein the modifier is made of trimesic acid, magnesium salt and tetrabutyl titanate. The underground goaf composite grouting material prepared by the present invention has improved compressive strength and flexural strength, and the flame retardant effect reaches a state of self-extinguishing from fire.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A composite grouting material for underground goaf, characterized in that: The underground goaf composite grouting material is made of component A and component B, and the weight ratio of component A to component B is 0.6-1.1:1; The component A comprises the following raw materials in parts by weight: 50-100 parts of polyol, 0.3-0.8 parts of foaming agent, 1.5-3 parts of catalyst, 120-150 parts of ordinary Portland cement, and 60-80 parts of water; The B component includes the following raw materials in parts by weight: 35-55 parts of polyisocyanate, 35-50 parts of reinforcing agent, 2-8 parts of modifier, and 5-15 parts of flame retardant; The modifier is made of trimesic acid, magnesium salt and tetrabutyl titanate.
2. The underground goaf composite grouting material according to claim 1, characterized in that: The polyol is polyether polyol and / or polyester polyol.
3. The underground goaf composite grouting material according to claim 1 or 2, characterized in that: The foaming agent comprises one or more of monofluorodichloroethane, trifluorodichloroethane, trifluorotrichloroethane, pentafluoropropane, pentachlorobutane, cyclopentane, n-pentane and perfluoroheptane.
4. The underground goaf composite grouting material according to claim 3, characterized in that: The catalyst is an organic metal catalyst and an amine catalyst; the organic metal catalyst is stannous octoate, dibutyltin dilaurate or bismuth isooctanoate; the amine catalyst is triethylenediamine, N,N-dimethylcyclohexylamine, triethylenediamine, triethanolamine or pentamethyldiethylenetriamine.
5. The underground goaf composite grouting material according to claim 2 or 4, characterized in that: The polyisocyanate comprises one or more of toluene-2,4-diisocyanate, carbodiimide-modified diphenylmethane diisocyanate and isophorone diisocyanate.
6. The underground goaf composite grouting material according to claim 5, characterized in that: The reinforcing agent comprises one or more of nano calcium carbonate, nano silicon dioxide and glass fiber.
7. The underground goaf composite grouting material according to claim 1, 2, 4 or 6, characterized in that: The flame retardant comprises one or more of triethyl phosphate, dimethyl methyl phosphate, triisopropylphenyl phosphate, dibromoneopentyl glycol, ammonium polyphosphate and ammonium molybdate.
8. The underground goaf composite grouting material according to claim 7, characterized in that: The preparation method of the modifier comprises the following steps: tetrabutyl titanate, magnesium salt and trimesic acid are mixed in methanol to carry out solvent thermal reaction to prepare the modifier.
9. The underground goaf composite grouting material according to claim 8, characterized in that: The mass ratio of tetrabutyl titanate, magnesium salt and trimesic acid is 3-5:1-4:1-3; the mass volume ratio of magnesium salt and methanol is 1-4g:50-120mL; the temperature of the solvent thermal reaction is 100-120°C, and the time of the solvent thermal reaction is 1-3h.
10. The method for preparing the composite grouting material for underground goaf according to any one of claims 1 to 9, characterized in that: The steps include: (1) ordinary Portland cement and water are mixed, and then a polyol, a foaming agent and a catalyst are added and mixed to obtain component A; (2) mixing polyisocyanate, reinforcing agent, modifier and flame retardant to obtain component B; (3) Component A and component B are mixed according to a weight ratio to obtain a composite grouting material for underground goaf areas.